The Behavior of Dissolved Gas in Mineral Oil with TiO2 and Three Types of Insulation Paper at 150 Degree Celsius - Korraya Jongvilaikasem; Chanin Bunlaksananusorn; Wanwilai Vittayakorn; Norasage Pattanadech (My University, 2024)
The main electrical insulation in oil-immersed transformers is liquid insulation and paper insulation. Liquid insulation is generally used mineral oil. However, improvements in the quality of liquid insulation are continually being made for better efficiency i.e. adding various additives such as inhibitors and nanoparticles. Nanoparticles are a solid substance used in research for many years. TiO2 is a type of nano that is commonly used in research to increase the efficiency of mineral oil. This research experimented by preparing dry transformer oil mixed with 0.03% TiO2. The test vessels consisted of 3 main components: 1) 35 ml of MO with 0.03% TiO2, 2) 1 gram of paper with three types of insulation including pressboard, kraft, and diamond dot paper, and 3) two types of coils including copper and aluminum with size 1*2.5 cm. The sample vessels were aged at 150 C for 72 hours in the vacuum oven. After aging, oil samples were analyzed by dissolved gas analysis (DGA). From the DGA test results, it was found that similar weights of different types of paper produced different gas-generating results.
Keywords: Aerogels and thermal insulation; High voltage insulation and dielectric phenomena